Metronome Cueing of Walking Reduces Gait Variability after a Cerebellar Stroke - Wright, Rachel L.; Bevins, Joseph W.; Pratt, David; Sackley, Catherine M.; Wing, Alan M. (Frontiers in Neurology, 2016)
Cerebellar stroke typically results in increased variability during walking. Previous research has suggested that auditory-cueing reduces excessive variability in conditions such as Parkinson’s disease and post-stroke hemiparesis. The aim of this case report was to investigate whether the use of a metronome cue during walking could reduce excessive variability in gait parameters after a cerebellar stroke. An elderly female with a history of cerebellar stroke and recurrent falling undertook 3 standard gait trials and 3 gait trials with an auditory metronome. A Vicon system was used to collect 3-D marker trajectory data. The coefficient of variation was calculated for temporal and spatial gait parameters. Standard deviations of the joint angles were calculated and used to give a measure of joint kinematic variability. Step time, stance time and double support time variability were reduced with metronome cueing. Variability in the sagittal hip, knee and ankle angles were reduced to normal values when walking to the metronome. In summary, metronome cueing resulted in a decrease in variability for step, stance and double support times and joint kinematics. Further research is needed to establish whether a metronome may be useful in gait rehabilitation after cerebellar stroke, and whether this leads to a decreased risk of falling.